Factors Influencing The Capital Structure Of Shari'ah Compliant Public Listed Companies In The Kuala Lumpur Stock Exchange (KLSE). - Digale, Abdi Aziz Ahmed (2009)
The understanding of the Shari'ah principles is one of the most important issues that companies must learn and train their employee to be clear towards the rules and regulations of Shari'ah to practice as its is. Hence the Shari'ah is universal for all humankind, its settles all the issues that human beings face in this world whether its business or other things. The Shari'ah is built on two basic principles, namely: removal of hardship(ra 'f alharaj) and the prevention of haram ( daf' aldarar) (Rosly 2005). This has direct bearing to the Qur'anic verse that "God never intended to make religion a means of inflicting hardship" (22:78) and "God intends to make easy for you" ( 4:28).